M. C. Turtle and the hip hop hare : a nursery rap - Vozar, David (Doubleday Book for Young Readers, 1995)
Hip Hop Hare challenges M.C.Turtle to a race along the city streets in this rap version of "The Tortoise and the Hare".mpty Dumpty, and Little Bo-Peep.